MANAGEMENT STRATEGIES FOR IMPROVING THE SYSTEM OF PHYSICAL EDUCATION IN SCHOOL (University Arena, 2025)
Building and maintaining student interest in the movement and exercise are priority tasks of physical education teacher.Objectives. In this regard, we have proposed lines of research, methods of optimization of educational process organization based physical education lessons using athletic training means.Methods. The methods used in the research are: observation method, with which we evaluated the effects of systematic physical education teaching method used to present concrete demonstration exercises collective experiment method; data comparison method, the measurement method and the results of the test subjects;Results. Special training programs athlete greenhouse multilateral training took into account mainly the composition and organization of cycles of lessons that were based on a number of objective and subjective factors related to growth processes and phenomena functional of schoolchildren.Conclusion. Studying theory and practice of educational process of physical education in the secondary school shows that so far curricula contain general elements and not oriented well established for such trainings with very few embodiments enabling a progressive development functional parameters of students.